Towards circular economy through novel waste recycling technologies - Kristina Bazienė; Justinas Gargasas; Surya Rajendran; Jordan Nathan Solomon (Entrepreneurship and Sustainability Issues)
The shift towards a circular economy is gaining momentum as a crucial strategy to address environmental sustainability challenges, particularly the growing concerns related to waste management and resource depletion. In this context, novel waste recycling technologies are emerging as vital components in transforming waste into valuable resources, closing the loop in production and consumption cycles. Traditional linear 'take, make, dispose' systems are being replaced by innovative technologies that aim to reduce waste generation, extend product life, and recover resources from end-of-life products. This paper explores the role of new waste recycling technologies in advancing the circular economy. Key technologies such as pyrolysis, hydrothermal liquefaction, chemical recycling, and biotechnological approaches are discussed for their potential to handle diverse waste streams, including plastics, electronics, and organic. Each technology is evaluated in terms of its ability to convert waste into valuable secondary raw materials like fuels, chemicals, and bioplastics, and its contributions to reducing environmental footprints. Furthermore, the paper highlights integrating these technologies within the circular economy framework, focusing on how they contribute to reducing reliance on virgin resources, minimising waste sent to landfills, and decreasing carbon emissions. Case studies are presented to demonstrate successful applications of novel recycling methods in industry, showing their scalability, economic viability, and environmental benefits. In conclusion, novel waste recycling technologies are essential for achieving the objectives of a circular economy, offering pathways to a more sustainable and resource-efficient future. However, further research, policy support, and technological development are needed to overcome challenges such as economic feasibility, regulatory barriers, and technological scalability, ensuring that these innovations can be effectively integrated into global waste management systems.